Complications and post-operative sequelae of temporomandibular joint arthrocentesis. Issue 4 (4th July 2018) - Vaira, Luigi Angelo; Raho, Maria Teresa; Soma, Damiano; Salzano, Giovanni; Dell'aversana Orabona, Giovanni; Piombino, Pasquale; De Riu, Giacomo
Abstract: Objective:  To evaluate intraoperative complications and postsurgical sequelae associated with arthrocentesis of the TMJ, including injection of Sodium Hyaluronate. Methods: This retrospective study evaluated 433 arthrocentesis procedures performed in 315 patients between January 2009 and August 2016. The authors reviewed the complications identified during the procedure and the follow-up period. Results: Temporary swelling of the periarticular tissues (95.1%) or the external auditory canal (23.5%), ipsilateral temporary open bite (68.8%), frontalis and orbicularis oculis paresis (65.1%), preauricular hematoma (0.4%), and a case of vertigo (0.2%) were the complications detected. Conclusions: TMJ arthrocentesis remains a procedure with a minimum number of important complications. If present, complications are generally temporary, caused by the anesthetic effect or by the soft tissue edema created by the fluid extravasation created by the irrigation procedure, and can be managed on an outpatient basis.